Early onset Charcot‐Marie‐Tooth neuropathy type 2A and severe developmental delay: expanding the clinical phenotype of MFN2‐related neuropathy. Issue 4 (December 2015) - Tufano, Maria; Cappuccio, Gerarda; Terrone, Gaetano; Manganelli, Fiore; Pisciotta, Chiara; Geroldi, Alessandro; Capponi, Simona; Del Giudice, Ennio
Abstract: Charcot‐Marie‐Tooth (CMT) syndromes are a group of clinically heterogeneous disorders of the peripheral nervous system. Mutations of mitofusin 2 (MFN2) have been recognized to be associated with CMT type 2A (CMT2A). CMT2A is primarily an axonal disorder resulting in motor and sensory neuropathy. We report a male child with psychomotor delay, dysmorphic features, and weakness of lower limbs associated with electrophysiological features of severe, sensory‐motor, axonal neuropathy. The patient was diagnosed with early onset CMT2A and severe psychomotor retardation associated with c.310C>T mutation (p.R104W) in MFN2 gene. CMT2A should be considered in patients with both axonal sensory‐motor neuropathy and developmental delay.